Xp11.2 Duplication in Females: Unique Features of a Rare Copy Number Variation - Czakó, Márta; Till, Ágnes; Zima, Judith; Zsigmond, Anna; Szabó, András; Maász, Anita; Melegh, Béla; Hadzsiev, Kinga (Frontiers in Genetics, 2021)
Among the diseases with X-linked inheritance and intellectual disability, duplication of the Xp11.23p11.22 region is indeed a rare phenomenon, with less than 90 cases known in the literature. Most of them have been recognized with the routine application of array techniques, as these copy number variations are highly variable in size, occurring in recurrent and non-recurrent forms. Its pathogenic role is not debated anymore, but the information available about the pathomechanism, especially in affected females, is still very limited. It has been observed that the phenotype in females varies from normal to severe, which does not correlate with the size of the duplication or the genes involved, and which makes it very difficult to give an individual prognosis. Among the patients studied by the authors because of intellectual disability, epilepsy, and minor anomalies, overlapping duplications affecting the Xp11.23p11.22 region were detected in three females. Based on our detailed phenotype analysis, we concluded that Xp11.23p11.22 duplication is a neurodevelopmental disorder.